Evaluasi Kualitas E-Voting Berbasis Kriptografi Terdistribusi Berdasarkan Standar ISO/IEC 25010 - Akbar, Ahmad Fauzi; Makmur, Amelia; Yohannis, Alfa Ryano (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
As an antithesis to the implementation of electronic voting systems based on expensive server infrastructure, this research offers a novelty in the form of pure client-side cryptography to guarantee data security in a zero-cost environment. This study evaluates the quality and acceptance of a zero-cost serverless e-voting system secured by distributed cryptography. The assessment utilized Black Box testing, ISO/IEC 25010 quality standards, and a modified Technology Acceptance Model (TAM) integrating Trust as the primary antecedent. Built on a serverless architecture (Google Apps Script), the system uses client-side AES-256 and SHA-256 encryption algorithms. A sequential explanatory mixed-methods design was applied. Quantitative data from 100 students at SMKN 7 Tangerang Regency, selected through rigorous criteria, was triangulated with qualitative IT administrator interviews. Functional testing showed a 100% success rate. The ISO/IEC 25010 evaluation categorized the system as "Highly Feasible", scoring 88.1% in Functional Suitability, 88.4% in Usability, and 87.4% in Security. PLS-SEM inferential analysis proved that perceived security significantly mediates user Trust (T-Statistics: 7.518). Interestingly, an anomaly was found where Perceived Usefulness was overwhelmingly driven by interface practicality rather than trust. This study proves that high-level data protection can be achieved without dependence on large infrastructure budgets